Comparative evaluation of intracanal cryotherapy and curcumin as a final irrigant in reducing post endodontic pain in primary teeth - Nimisha Kumari; Harsimran Kaur; Rishika Choudhary; Ramakrishna Yeluri (Wolters Kluwer Medknow Publications, 2022)
Aim: The aim of this study was to evaluate the intracanal effectiveness of cryotherapy, curcumin irrigant, and normal saline as a final irrigant in reducing postendodontic pain in primary teeth. Materials and Methods: A total of 120 teeth between the ages of 4 and 7 years requiring pulpectomy in primary teeth were included in the study. The teeth were randomly assigned to one of the three treatment groups: intracanal cryotherapy using 2.5°C cold saline, curcumin irrigant, or normal saline. Following completion of chemomechanical preparation, final irrigation with 2.5°C cold saline, curcumin irrigant, and normal saline solution at room temperature were employed in the groups. Participants were asked to rate the severity of their postoperative pain on the Visual Analog Scale before, immediate postoperative after wearing of local anesthetic effect, and 24 h after the procedure. The results were analyzed statistically. Results: The differences in reduction of postendodontic pain between the three irrigating regimens were statistically not significant. Cryotherapy utilizing 2.5°C cold saline or curcumin irrigant can be used instead of normal saline as a final irrigant in pulpectomy of primary teeth. Conclusions: Cryotherapy can be a straightforward, cost-effective, and nontoxic treatment option for the management of postendodontic pain. Curcumin irrigant with its anti-inflammatory properties is also a better alternative as a final irrigant for reducing postoperative pain in primary teeth.